Multidisciplinary Emergency Management of Severe Maternal Polytrauma With Early Fetal Demise and Delayed Sepsis: A Rare Case Report - Rochmanita Safitri; Erika Kusuma Santoso (International Medical Journal Corp. Ltd, 2026)
Introduction: Trauma during pregnancy poses significant diagnostic and therapeutic challenges, as physiological adaptations can obscure early signs of instability and increase both maternal and fetal vulnerability. High-energy blunt trauma often results in multisystem injuries involving the pelvis, thorax, diaphragm, and long bones. When these injuries occur in mid-pregnancy, the risk of intrauterine fetal demise rises sharply, and the complexity of maternal stabilization frequently delays obstetric intervention. Clear guidance on long-term management remains limited, especially when fetal demise is retained during recovery from extensive surgical trauma. Case Illustration: A pregnant woman in mid-gestation sustained severe multisystem injuries following high-impact blunt trauma. Her injuries included pelvic ring disruption, femoral and tibial fractures, hemothorax requiring thoracic drainage, and a left-sided traumatic diaphragmatic hernia with herniation of abdominal organs into the thoracic cavity. Early intrauterine fetal demise was identified shortly after resuscitation. She underwent thoracoabdominal surgery and orthopedic fixation, achieved postoperative stabilization, and was discharged in improving condition. Several days, she developed progressive abdominal pain, systemic deterioration, and severe sepsis. Imaging and clinical evaluation suggested that the retained fetal tissue, combined with prior thoracoabdominal and orthopedic injuries, contributed to the delayed infectious complication. She underwent uterine evacuation and intensive management, leading to eventual clinical improvement. Discussion: This case illustrates how multisystem trauma in pregnancy can generate a prolonged and unpredictable clinical trajectory. The need to prioritize maternal stabilization often necessitates delaying uterine evacuation, yet retained fetal demise, especially in patients recovering from major surgery, may predispose to delayed sepsis. This interplay between trauma physiology, surgical recovery, and obstetric timing highlights a critical gap in current guidelines. The case underscores the importance of multidisciplinary coordination, extended monitoring beyond initial discharge, and heightened vigilance for delayed infectious complications. Conclusion: Severe maternal trauma with concurrent pelvic, thoracic, and diaphragmatic injuries requires individualized, maternal-centered care. When fetal demise occurs, timing of evacuation must balance surgical risk with the potential for long-term complications. This case emphasizes the need for structured follow-up and clearer clinical pathways to prevent delayed sepsis in similar high-risk presentations.